Estado compuesto y corresponsabilidad policial. Un análisis comparado de los sistemas de seguridad pública español, alemán y canadiense - Carmona Pérez, Carlos (Revista del CLAD Reforma y Democracia, 2018)
AbstractOne of the pillars that support the composite states is the principle of police co-responsibility in the public security system. From an empirical perspective, this principle assumes decentralized approaches of the police action aimed at the effectiveness, efficiency and the precept of territorial unit of public security. This study analyzes from a comparative perspective the shared responsibility of the police in the Spanish system of public security with other models of the composite State such as Germany and Canada. The main objective of the comparison between these three models is based on the focalization of potential elements of integration and differentiation that allow knowing the idiosyncrasies of the co-responsible police action between the different levels of government.
Keywords: State; Public Security; Responsibility; Police; Intergovernmental Relations; Spain; Germany; Canada